2012
DOI: 10.1007/s10164-012-0353-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selection for behavior, human approach mode and sex on vocalization in silver fox

Abstract: This study presents a first direct comparison of vocal type, call rate and time spent vocalizing among Unselected, Tame and Aggressive strains of silver fox (Vulpes vulpes) in three modes of human approach (Provoking, Approach–Retreat, and Static). Also, it provides a first comparison of male and female vocal output in the Provoking test. Vocal types were found strain-specific irrespective of the fox sex or the test. Males had higher call rates and spent shorter times vocalizing than females. These results sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 30 publications
(54 reference statements)
1
14
1
4
Order By: Relevance
“…This is different from studies on other animal species, which show that animal gender may be identified by sound signals (BALSBY & ADAMS, 2011;MATROSOVA et al, 2011;GOGOLEVA et al, 2012).…”
Section: Resultscontrasting
confidence: 65%
“…This is different from studies on other animal species, which show that animal gender may be identified by sound signals (BALSBY & ADAMS, 2011;MATROSOVA et al, 2011;GOGOLEVA et al, 2012).…”
Section: Resultscontrasting
confidence: 65%
“…В 5-минутном Провоцирующем тесте воздействие человека было не дозировано и продолжалось до достижения животными порога кричания (Gogoleva et al, 2008(Gogoleva et al, , 2013. За-пись звуков начиналась, когда наблюдатель подходил на расстояние 0.5-1 м до клетки фокального животного и продолжалась в течение 4-6 мин, пока наблюдатель нахо-дился перед клеткой.…”
Section: материал и методыunclassified
“…Тест Приближения -удаления состоял из пяти 2-минутных ступеней и начинался в момент под-хода исследователя к клетке фокальной лисицы на рас-стояние 0.5 м. На 1-й ступени исследователь оставался не подвижным; на 2-й ступени он совершал плавные дви-жения телом и рукой из стороны в сторону, оставаясь на расстоянии 0.5 м; на 3-й ступени сокращал дистанцию, делая шаг вперед, и совершал движения телом и рукой впе-ред и назад, касаясь пальцами дверцы клетки; 4-я ступень полностью совпадала со 2-й ступенью, а 5-я копировала 1-ю ступень. В 5-минутном Статичном тесте воздействие со стороны человека было тоже одинаковым для всех лисиц и оставалось неизменным в течение всей записи (Gogoleva et al, 2011(Gogoleva et al, , 2013. Во время теста эксперимен-татор стоял в 0.5 м перед клеткой, выполняя однообразные движения рукой из стороны в сторону.…”
Section: материал и методыunclassified
See 2 more Smart Citations